Financing Women Entrepreneurs in Ethiopia - Strobbe, Francesco; Alibhai, Salman (World Bank, Washington, DC, 2016)
The challenges faced by women-owned enterprises in the developing world are substantial. Only one-third of the world’s SMEs in the formal sector are currently run by women, and women owned businesses typically underperform men’s. Across countries and contexts, access to finance is continuously identified as the leading constraint faced by women entrepreneurs. While finance is a challenge for male and female enterprises alike, the difficulties are amplified for women, who are less likely to own assets which can serve as collateral andare more likely to suffer exclusion based on unequal property rights or discriminatory regulations, laws and customs. An estimated 70 percent of women-owned SMEs in the formal sector in developing countries are unserved or underserved by financial institutions.This amounts to a financing gap of 285 billion dollars. A diverse range of economic research shows that addressing this financing gap and investing in women-owned enterprises is one of the highes treturn opportunities available in emerging markets.As they grow, women-owned enterprises enhance labor participation and boost broad-based economic growth. In particular, due to higher female unemployment rates and the fact that women are more likely to hire other women, the growth offemale-owned enterprises can be a key driver in reducing high overall unemployment rates.